Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

I substituted cotx= t in this question but I m still not getting the solution

I substituted cotx= t in this question but I m still not getting the solution

Question Image
Grade:11

1 Answers

Myra
12 Points
2 years ago
cotx = t
-cosec^2(x) dx =dt
dx = -dt/cosec^2(x)=-dt(sin^2x)
Substitute 
∫ 1  dx                 = ∫-sinx dt
————                  ——————
sinx√sinx√cosx    √sinx√cosx
 
= -∫ √tanx dx
=-∫1/√t dt = -2 √cotx +c
 
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free